PROSES MANAJEMEN PENDIDIKAN DI PONDOK PESANTREN DAARUDDA’WAH KABUPATEN TASIKMALAYA - Windriyana Windriyana; Franciskus Antonius Alijoyo (Universitas Bina Taruna Gorontalo, 2024)
This research aims to study new and creative educational management practices in facing the challenges of the digital era, with a focus on secondary Islamic boarding schools in Indonesia. The research method used is qualitative with a case study approach at selected Daruddwah Islamic boarding schools. Data was collected through interviews with informants, observations at research location, and analysis of related documents. The research results show that the use of technology in Islamic boarding school management not only makes administrative work more efficient, but also improves the quality of learning. The innovations found include the use of digital learning management systems, the application of mixed learning methods, and increasing teachers' abilities in using technology. However, the research also found challenges, such as limited access to technology and differences in the level of digital readiness between teachers and students. This research provides understanding of how Islamic boarding schools can change management practices to exploit the potential of education in the digital era, and provide recommendations for educational policy and teacher professional development.